REASONS FOR THE ENTRY OF STUDENTS IN TECHNICAL EDUCATION OF HIGH LEVEL - Augusto, Emerson Aparecido (Revista Interface Tecnológica, 2023)
This research aims to identify, through the perception of incoming students, the motivations and reasons that justify or explain their choices for vocational education courses in high school technical education, and to understand the role of technical education from the students’ point of view. Some theoretical support will be necessary in the studies, in order to understand the reality experienced by the participants throughout their school trajectories, the motivations and expectations generated in relation to the educational and professional future, their reasons for choosing high school technical training and their relationships with the chosen formation. The present study helped to identify the real reason that led students to join the technical course and, in this way, will contribute to the organization of decision-making processes in the final grades of elementary school, at which time other students will be able to define the professional path of their lives. It was also verified the importance of complementing the students’ education, making it clear what are the educational objectives in the classroom and how to develop them so that students effectively learn.